Eksplorasi Aktivitas Antioksidan dan Profil Fenolik dari Ekstrak dan Fraksi Daun Lantana camara L - Yoan De Nanda Herru; Adlis Santoni; Suryati Suryati; Anna Anggraini; Rahmi Vika Ulia (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
This study aimed to evaluate the antioxidant activity and total phenolic content of methanolic extract and column chromatography fractions of Lantana camara L. leaves. Antioxidant activity was assessed using the DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging method, while total phenolic content was determined by the Folin–Ciocalteu assay. The methanolic extract exhibited strong antioxidant activity (IC₅₀ = 23.25 mg/L) and a total phenolic content of 2927.4 mg/L gallic acid equivalents (GAE). Fractionation yielded nine fractions (A–I), among which Fraction E demonstrated the highest antioxidant activity (IC₅₀ = 11.58 mg/L) and the greatest phenolic content (5200 mg/L GAE). A strong negative correlation (R² = 0.9485) was observed between phenolic content and IC₅₀ values, indicating that phenolic compounds are the major contributors to the antioxidant activity. These findings highlight L. camara leaves as a promising natural source of antioxidants and support their potential application in the development of functional foods and plant-based pharmaceutical formulations.